A nonlinear constrained optimization model for subsea pipe route selection on an undulating seabed with multiple obstacles. (15th August 2019) - Hong, Cheng; Estefen, Segen F.; Lourenço, Marcelo Igor; Wang, Yuxi
Abstract: Subsea pipe route selection is very complex which involves several issues due to the complicated sea environment. A properly selected subsea pipe route could help reduce costs and meet engineering requirements. While simultaneously considering the related requirements, this task becomes a complicated optimization problem. This paper proposes a nonlinear constrained optimization model for selecting pipe route with minimum length that considers seabed topography, obstacles and pipe curvature requirements. Besides, the process of determining the intersection between the pipe route and obstacles is presented. The Particle Swarm Optimization based Augmented Lagrangian multiplier method followed by dynamic programming is applied to solve the proposed model. Both flat and undulating seabed with obstacles were considered for the case studies, and the proposed model was compared with Dijkstra algorithm, indicating the feasibility, stability and reliability of the proposed model and solution method. This work provides an initial understanding of pipe route optimization, and other engineering requirements related to safety and cost can be easily added to the proposed model, making the proposed model flexible to the needs of users for different application scenarios. Highlights: A nonlinear constrained optimization model is proposed to select the subsea pipe route. Seabed topography, obstacles, pipe line curvature are taken into consideration PSO method, Augmented Lagrangian multiplier method, dynamic programming are applied. The proposed model was compared with the Dijkstra algorithm. The work could be extended to link other related issues for further optimization.